(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Gender equality education in literature learning is becoming increasingly significant due to the growing awareness. Gender equality education in literature learning has become increasingly important due to the growing awareness of gender stereotypes and biases within educational settings. This article examines how Serat Candrarini, as a classical Javanese literary text, represents gender relations through patterns of binary opposition and explores its implications for gender-equitable education. The study employs a qualitative descriptive method using content analysis and a feminist deconstruction approach. The findings indicate that gender relations in the text are constructed through oppositions such as active–passive, high–low, and rational–emotional, positioning women in a subordinate role. However, the text also reveals small spaces that allow for critical readings of patriarchal values. These findings underscore the importance of reflective literature learning that fosters shifts in perspectives toward gender equality. Integrating gender perspectives into the curriculum and teaching methods is an essential step in cultivating awareness of educational equality. Further research is recommended to explore other traditional texts and to develop practical, gender-based literacy learning modules.